Systematic Literature Review: Efektivitas Peningkatan Literasi Matematika Peserta didik Melalui Media Komik - Iin Ariyas Setyawati; Bambang Eko Susilo (Universitas Muhammadiyah Magelang, 2026)
This study aims to describe the results of research related to mathematics learning using comics or e-comics to improve students' mathematical literacy. The research method used is the Systematic Literature Review (SLR) method. The article search process utilized the Harzing's Publish or Perish application and the research data source came from the Google Scholar platform with a publication range of 2021-2025. The literature screening process used the PRISMA 2020 guidelines which include the identification, screening, and inclusion stages. The results show that research related to the application of comic media in mathematics learning to improve students' mathematical literacy has received quite good attention in recent years. This is further evidenced by the increase in research in 2025, where research is mostly conducted at the junior high school level with the most frequently chosen subject matter being geometry and algebra. The most research was conducted in Java and Sumatra. The most widely used research method is the development method (Research and Development) with digital comics as the most frequently chosen media type. Mathematics learning using comic media is effective for improving students' mathematical literacy.